2020
DOI: 10.5897/ajpp2020.5123
|View full text |Cite
|
Sign up to set email alerts
|

Prescribing pattern of medications prescribed to outpatients based on WHO prescribing indicators in Ethiopia: A systematic review and meta-analysis of observational studies

Abstract: Poor prescribing pattern is observed and become a serious problem in the world including developing countries. In Ethiopia, several studies showed that health care institutions did not meet WHO prescribing indicators and the prescribing pattern is not satisfactory in the health care institutions. This study aimsto review the prescribing pattern of medications prescribed to outpatients based on WHO prescribing indicators in Ethiopia. Literature search was performed through PubMed/MEDLINE, Google Scholar, and Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 7 publications
3
8
2
Order By: Relevance
“…This is slightly higher than the standard comparison (1.6-1.8). 6 This result is consistent with two prior studies that conducted systematic reviews at the country level in Ethiopia and found that the pooled number of drugs per prescription exceeded WHO standards, accounting for 1.96 and 2.14, respectively, Ayenew et al 20 and Bahiru et al 21 respectively. Poly-pharmacy was also recorded in the city as well as different parts of the country, according to study setting specialized studies.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…This is slightly higher than the standard comparison (1.6-1.8). 6 This result is consistent with two prior studies that conducted systematic reviews at the country level in Ethiopia and found that the pooled number of drugs per prescription exceeded WHO standards, accounting for 1.96 and 2.14, respectively, Ayenew et al 20 and Bahiru et al 21 respectively. Poly-pharmacy was also recorded in the city as well as different parts of the country, according to study setting specialized studies.…”
Section: Discussionsupporting
confidence: 85%
“…34 In the current study, the proportion of encounters in which injections were issued was 11.5%, which is signi cantly lower than the WHO criterion (13-24.1%). 6 Ethiopian injection use is likewise below the standard, according to the combined results 18.3%, 13.2% of Ayenew et al 20 and Bahiru et al 21 respectively. There has also been a global drop in injection usage.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Another systematic review and meta-analysis also reported that all of the prescribing indicators were not consistent with the standard values [ 20 ]. The practice of rational medicine use varied across the region of the country and deviation was also reported from the standard recommended by WHO [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%